MiR-148b-3p Regulates the Expression of DTYMK to Drive Hepatocellular Carcinoma Cell Proliferation and Metastasis - He, Guifang; Qiu, Jing; Liu, Changchang; Tian, Ben; Cai, Duo; Liu, Shihai (Frontiers in Oncology, 2021)
Deoxythymidilate kinase (DTYMK) has been identified as a putative oncogene associated with the incidence of hepatocellular carcinoma (HCC), but the mechanisms whereby it regulates this cancer type remain uncertain. The present study was therefore designed to explore the role of DTYMK in HCC and to evaluate the underlying molecular mechanisms. MiRNAs associated with DTYMK expression levels in HCC were identified through analyses of both clinical samples and publically available gene expression datasets. We then assessed the putative functions of DTYMK and miR-148b-3p in this oncogenic context through studies of HCC cells and a murine xenograft model system. Correlation analyses and in vitro experiments led us to confirm DTYMK as a target of miR-148b-3p. In addition, we assessed dTTP levels associated with the DTYMK pathway in HCC cells to understand the functional implications of our experimental findings. We found that HCC tissues and cells exhibited marked DTYMK upregulation and miR-148b-3p downregulation, with the expression levels of DTYMK and miR-148-3p being negatively correlated with one another. The impact of overexpressing DTYMK in tumor cells was partially reversed upon cellular transfection with miR-148b-3p mimics, providing conclusive evidence that DTMYK is a target of this miRNA. Importantly, DTYMK-related dTTP levels were also impacted by miR-148b-3p mimic transfection. DTYMK is a key regulator of HCC progression, and its expression is suppressed by miR-148b-3p, suggesting that this miR-148b-3p/DTYMK regulatory axis may be amenable to therapeutic targeting in patients with HCC.